Efikasi Diri Dan Manajemen Diri: Konseling Kelompok Sebagai Upaya Penyelesaian Masalah Siswa - Ningsih, Tria Harvia; Darmawani, Evia; Surtiyoni, Endang (Universitas Nusantara PGRI Kediri, 2023)
Self-efficacy is one of the things that everyone must have whereas self-efficacy is the belief that someone has to determine a decision in an action. Self-efficacy is closely related to self-management where self-management is a person's ability to monitor one's own thoughts, feelings, and behavior to achieve goals. Students, even adults, sometimes have low confidence, making it difficult to manage themselves because some of them are lazy, marked by students who find it difficult to respond. The purpose of this study was to determine the effect of group counseling on students' self-efficacy and self-management. This research is a type of quasi-experimental research that later analyzes the data using the Wilcoxon test. The sample of this research was 10 students who were in class VIII. The results showed that there was a significant influence on self-efficacy and self-management after giving group counseling and changing behavior with a value of Zcount > Ztable, namely -2.818b ≤ 0.005, it was said that Ha was accepted. Thus self-efficacy and self-management of students can be improved through group counseling.